2013
DOI: 10.1107/s0021889813005797
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and thermal properties of Zr–Fe co-doped congruent LiNbO3single crystals

Abstract: Zr–Fe‐doped congruent lithium niobate single crystals were grown by the Czochralski technique. The crystal structure and lattice parameter of the grown crystals were assessed by powder X‐ray diffraction and the strain developed as a result of doping has been calculated (−1.19 × 10−3) by using the Williamson–Hall relation. The incorporated dopant concentration along with the dopant distribution in the specimen crystal was estimated by X‐ray florescence spectrometry. A multi‐crystal X‐ray diffraction analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The DCs of CLN (Figure 5a) and nSLN_L (Figure 6a) consist of a single diffraction peak that signifies that these crystals are free from any internal sub-grain boundary [76][77][78], which is otherwise usually observed because of the strain generated during the post-growth cooling due to The DCs of the Mg-doped LN (Figure 5b-d) crystals contain a single diffraction peak. The full-width at half-maximum (FWHM) of the DCs estimated using curve fitting are 76, 112, and 65 arc-sec for 2.0, 4.0, and 6.0 mol % Mg doped samples respectively.…”
Section: Effect Of Defect Control Processes On Crystalline Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The DCs of CLN (Figure 5a) and nSLN_L (Figure 6a) consist of a single diffraction peak that signifies that these crystals are free from any internal sub-grain boundary [76][77][78], which is otherwise usually observed because of the strain generated during the post-growth cooling due to The DCs of the Mg-doped LN (Figure 5b-d) crystals contain a single diffraction peak. The full-width at half-maximum (FWHM) of the DCs estimated using curve fitting are 76, 112, and 65 arc-sec for 2.0, 4.0, and 6.0 mol % Mg doped samples respectively.…”
Section: Effect Of Defect Control Processes On Crystalline Qualitymentioning
confidence: 99%
“…In fact the cracking of the 6 mol % Mg doped crystal (6Mg:CLN) when grown with the pulling rate the same as that used for other compositions (2Mg:CLN and 4Mg:CLN) implies the presence of a relatively higher strain in that particular sample. The DCs of CLN ( Figure 5a) and nSLN_L ( Figure 6a) consist of a single diffraction peak that signifies that these crystals are free from any internal sub-grain boundary [76][77][78], which is otherwise usually observed because of the strain generated during the post-growth cooling due to structural phase transformation at~1140 • C (paraelectric to ferroelectric), growth imperfections, and instabilities. The FWHM of the DCs was evaluated by Lorentz fitting as tabulated in Table 2.…”
Section: Effect Of Defect Control Processes On Crystalline Qualitymentioning
confidence: 99%
“…Different types of dopants have been used for various applications of the LN crystals such as Mg, Zn, In, and Zr for suppressing the optical damage and metal ions like Fe, Mn, Cu, Ce, and Ru to improve photorefractive properties. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“…Generally, this property is thought to be related to the replacement of Zr 4+ ions against Nb 5+ on Li sites because the element Zr is adjacent to Nb in the periodic table. It has been reported that Zr 4+ ions co-dope with some transition metal elements in LN crystals [ 15 , 16 ], such as Fe, Mn, Cu, and Ce, which can considerably reduce the light-induced scattering as well as improve the response speed. Besides, Zr doping also improves the near infrared emission efficiency in LN:Er, LN:Yb,Er crystals [ 17 ]; meanwhile, it can also stabilize the signal output of the Ti-diffused LN waveguides under the high-power pumping without optical damage observed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%